A Novel Splice Variant of Human TGF-β Type II Receptor Encodes a Soluble Protein and Its Fc-Tagged Version Prevents Liver Fibrosis in vivo - Bertolio, Marcela Soledad; La Colla, Anabela; Carrea, Alejandra; Romo, Ana; Canziani, Gabriela; Echarte, Stella Maris; Campisano, Sabrina; Barletta, German Patricio; Monzon, Alexander Miguel; Rodríguez, Tania Melina; Chisari, Andrea Nancy; Dewey, Ricardo Alfredo (Frontiers in Cell and Developmental Biology, 2021)
We describe, for the first time, a new splice variant of the human TGF-β type II receptor (TβRII). The new transcript lacks 149 nucleotides, resulting in a frameshift and the emergence of an early stop codon, rendering a truncated mature protein of 57 amino acids. The predicted protein, lacking the transmembrane domain and with a distinctive 13 amino acid stretch at its C-terminus, was named TβRII-Soluble Endogenous (TβRII-SE). Binding predictions indicate that the novel 13 amino acid stretch interacts with all three TGF-β cognate ligands and generates a more extensive protein-protein interface than TβRII. TβRII-SE and human IgG1 Fc-domain, were fused in frame in a lentiviral vector (Lv) for further characterization. With this vector, we transduced 293T cells and purified TβRII-SE/Fc by A/G protein chromatography from conditioned medium. Immunoblotting revealed homogeneous bands of approximately 37 kDa (reduced) and 75 kDa (non-reduced), indicating that TβRII-SE/Fc is secreted as a disulphide-linked homodimer. Moreover, high affinity binding of TβRII-SE to the three TGF-β isoforms was confirmed by Surface Plasmon Resonance (SPR) analysis. Also, intrahepatic delivery of Lv.TβRII-SE/Fc in a carbon tetrachloride-induced liver fibrosis model revealed amelioration of liver injury and fibrosis. Our results indicate that TβRII-SE is a novel member of the TGF-β signaling pathway with distinctive characteristics. This novel protein offers an alternative for the prevention and treatment of pathologies caused by the overproduction of TGF-β ligands.